Outer membrane protein A of E. coli folds into detergent micelles, but not in the presence of monomeric detergent. - Kleinschmidt, J. H. (Cold Spring Harbor Laboratory Press, 1999)
Outer membrane protein A (OmpA) of Escherichia coli is a beta-barrel membrane protein that unfolds in 8 M urea to a random coil. OmpA refolds upon urea dilution in the presence of certain detergents or lipids. To examine the minimal requirements for secondary and tertiary structure formation in beta-barrel membrane proteins, folding of OmpA was studied as a function of the hydrophobic chain length, the chemical structure of the polar headgroup, and the concentration of a large array of amphiphiles. OmpA folded in the presence of detergents only above a critical minimal chain length of the apolar chain as determined by circular dichroism spectroscopy and a SDS-PAGE assay that measures tertiary structure formation. Details of the chemical structure of the polar headgroup were unimportant for folding. The minimal chain length required for folding correlated with the critical micelle concentration in each detergent series. Therefore, OmpA requires preformed detergent micelles for folding and does not adsorb monomeric detergent to its perimeter after folding. Formation of secondary and tertiary structure is thermodynamically coupled and strictly dependent on the interaction with aggregated amphiphiles.